History of Buildings From Hut to Highrise : Panorama - Macdonald, Fiona (East Sussex Macdonald Young Books, 1996)
A title from the PANORAMA series which examines buildings from prehistoric structure to late twentieth century high-tech buildings. Includes a frieze tracing the chronology of building across Europe, Japan and America. Suitable for National Curriculum Key Stage 2-3. Illustrated in full colour.
Include Color illustrations
Keywords: Buildings